Modeling sediment yield and deposition using the SWAT model: a case study of Cubuk I and Cubuk II reservoirs, Turkey - Duru, Umit, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Arabi, Mazdak, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2015)
Better understanding of which factors determine sediment yield rate to reservoirs can facilitate estimation of the probable lifespan of a reservoir and appropriate mitigation measures to limit reservoir sedimentation. Therefore, the research summarized here enhances understanding of correlations between potential control variables on suspended sediment yield and the resulting sediment yields to reservoirs. The Soil and Water Assessment Tool (SWAT) was applied to a portion of the Ankara River catchment, which comprises an area of 4932 km² in the central Anatolia region of Turkey. SWAT was calibrated and validated using monthly data from an upstream (1239 Ova Cayi – Eybek) sediment gaging site draining approximately 322 km². A local sensitivity analysis was performed on 18 and 22 input parameters in terms of model outputs such as water and sediment yields, respectively. The most sensitive model parameters affecting stream flow are GW_DEL (ground water delay time) and Alpha_BF (base-flow regression coefficient). For sediment yield, the most sensitive model parameters are SOL_Z (soil thickness), and CH_N1 (Manning coefficient of the channel). Besides these parameters, all other dominant hydrological parameters were determined and a reduction of the number of model parameters was performed in order to improve the Nash-Sutcliffe coefficient of efficiency and R². The SWAT model was performed to simulate water balance, stream flow, and sediment yield during recent decades. The Nash-Sutcliffe efficiency coefficient (NSE) and Relative Error were used to assess accuracy of the model. SWAT outputs indicate that the model performs well, because monthly stream flow of NSE= 0.79 and monthly suspended sediment load of NSE= 0.81 are within the acceptable range of RE and R², which are 0.58-1.55 (RE) and 0.89-0.93 (R²), respectively. According to multiple regression analysis, sediment yields in the watershed are dominantly influenced by stream flow, drainage area, and channel width. No other variables can be considered as prime control factors on sediment yield in the region. Finally, remote sensing and Geographic Information System software were used to assess sedimentation through time in the Cubuk I and Cubuk II reservoirs. Results indicate that a significant amount of siltation occurred between 1978 and 1983: Cubuk I reservoir accumulated 3 m of sediment within 6 years and Cubuk II accumulated about 10 m. Siltation is the most significant problem in the catchment, so efficient siltation management practices for the reservoirs should be performed to control sediment accumulation in these human made structures. However, there is considerable uncertainty associated with the model predictions in the Ankara Basin, due to lack of finer resolution soil data, as well as sediment stations for model parameterization, calibration, and validation. Future studies in the Cubuk catchment should focus on improving the database by obtaining higher resolution soil data and more accurate climate data, which will likely help to reduce model uncertainty. Testing the applicability of the SWAT model in the watershed and identifying the source of uncertainty has laid the groundwork for further research in the region.